2015
DOI: 10.5812/jjm.17520
|View full text |Cite
|
Sign up to set email alerts
|

The FimH Gene in Uropathogenic Escherichiacoli Strains Isolated From Patient With Urinary Tract Infection

Abstract: Background:Urinary tract infections (UTIs) are one of main health problems caused by many microorganisms, including uropathogenic Escherichia coli (UPEC). UPEC strains are the most frequent pathogens responsible for 85% and 50% of community and hospital acquired UTIs, respectively. UPEC strains have special virulence factors, including type 1 fimbriae, which can result in worsening of UTIs.Objectives:This study was performed to detect type 1 fimbriae (the FimH gene) among UPEC strains by molecular method.Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 16 publications
3
33
0
Order By: Relevance
“…Confocal laser scanning microscopy (CLSM) was performed to visualize effect of auranofin on biofilm. The importance of fimH and rpoS genes for UPEC infection has been suggested previously (Adnan et al ; Schwan ; Hryckowian and Welch ; Hojati et al ). However, it remains unclear how auranofin affects type 1 fimbriae gene ( fimH ) and response regulator gene ( rpoS ) to stress.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Confocal laser scanning microscopy (CLSM) was performed to visualize effect of auranofin on biofilm. The importance of fimH and rpoS genes for UPEC infection has been suggested previously (Adnan et al ; Schwan ; Hryckowian and Welch ; Hojati et al ). However, it remains unclear how auranofin affects type 1 fimbriae gene ( fimH ) and response regulator gene ( rpoS ) to stress.…”
Section: Introductionsupporting
confidence: 53%
“…The upregulation of rpoS gene might be for maintaining biofilm structure. Type 1 fimbriae gene fimH is an important gene involved in UPEC adhesion (Hojati et al ). Our qRT‐PCR results showed that expression levels of fimH gene were decreased when the concentration of auranofin was increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most clinical isolates of coliforms express type 1 (mannose-sensitive) and type 3 (mannose-resistant) fimbrial adhesins. Among adhesions of uropathogenic E. coli ,the adhesive subunit of type 1 fimbriae ,FimH, is a major determinant ,which has high tropism for urinary tract receptors ;thus, FimH adhesion is important in colonizing different niches of E. coli ( Hojati et al, 2015 ). Type 3 fimbrial adhesins are able to mediate the binding of K. pneumonia to various human cells , such as endothelial cells , epithelial cells of the respiratory tract and urinary tract .…”
Section: Introductionmentioning
confidence: 99%
“…The sediments were suspended in 500 µL of sterile deionized water, and boiled for 10 minutes. After centrifugation of the boiled samples at 19000 g for 5 minutes, the supernatant was used as DNA template in PCR assay (14).…”
Section: Dna Extraction From Culture For Pcrmentioning
confidence: 99%